Regional Geodynamic Implications of Proterozoic Volcanic and Metasedimentary Sequences in The Kirana Hills, Punjab, Pakistan - Talal Ahmed; Hassan, Iqra (Geological Agency, 2025)
The Proterozoic volcanic and metasedimentary sequences of Kirana Hills, Punjab, Pakistan, provide critical insights into the region geodynamic evolution of the northwestern margin of The Indian Shield. This study investigates the region stratigraphy, structural framework, and lithological variations of The Kirana Complex, and analyzes fracture studies to reconstruct regional geodynamic processes. The aim of this research is placed on understanding how volcanic and metasedimentary assemblages, along with deformation patterns, reflect the tectonic settings and subsequent crustal evolution of the area dated back to approximately 870 ± 40 million years. The studied region field investigations, geological mapping, and fracture analyses were combined with factor-mapped datasets. Fracture characterization was performed using circle inventory methods for the three sites to quantify structural orientation, density, porosity, and permeability. The rose diagram interpretation for the fracture analysis study was performed using permeability, and using the circle inventory method to understand tectonic deformation and fluid movement. The findings suggest that the region is exposed to Proterozoic sequences of volcanic rocks dominated mostly by rhyolite, basalt, dolerite, quartzite, and volcanogenic slates of mostly Hachi Volcanics and Mach Super Group with distinct evidence of multiple magmatic and tectono-metamorphic phases. Field evidence of felsic-mafic associations, mineralization (hematite, limonite, micaceous hematite, jasper, and bornite), and other alterations highlight fluid-rock interaction and multiple shifts of mineralization. The fracture studies show (i). Hadda Quartzite shows N-S oriented conjugate fractures associated with compressive stress and migration of paleo-fluids; (ii). In the Buland Hill Formation, there is evidence of radial and concentric fractures around volcanic vents with mineralized joints that indicate signs of hydrothermal activity; and (iii). The Foliation-aligned fractures of The Asianwala Formation suggest the related foliation-based shear deformation. Taken together, these characteristics point to the existence of an initial history of extensional regimes associated with continental rifting, then compressional reworking and progressive deformation. This work lies in its integration of fracture analysis study with regional structural and lithological studies and mapping of site characterization during the field analysis. This approach refines existing models of Kirana by linking fracture-controlled fluid migration to broader geodynamic processes.